District land development in Kherson government - Zaiets, O. V. (History of science and technology, 2016)
The experience of local self-governing in the South of Ukraine, particularly in district land development in Kherson government (1864−1917), is being studied. Forest protection activities consisted in severe penalties for unauthorized deforestation in favor of district and benefits systems for afforestation by private owners. The articles and reports about forest profit in water retention in soils and for crop yield increasing published both in district and in local periodicals. The district in every possible way popularized the A. A. De-Carrier’s experiment in 80-90’s of the XIX century, when in the most unfavorable highest part of the estate the afforestation had been accomplished in the form of two parallel stripes, between them grain crops were being sown. Regularly the district activities in ravines afforesting were being implemented.